Prevalence and Risk Factors for Hypovitaminosis D among Healthy Adolescents in Kota Bharu, Kelantan - Hussain, Suhaimi; Elnajeh, Maged (Journal of the ASEAN Federation of Endocrine Societies, 2020)
<center> </center><center></center><center> </center><center>*Visual Abstracts prepared by Dr. Jerico Gutierrez</center> Objective. We aim to study the prevalence and risk factors of hypovitaminosis D among healthy adolescents in Kota Bharu, Kelantan based on the most recent Paediatric Consensus guideline. Methodology. Ten public schools were selected from Kota Bharu, Kelantan. We analysed their demography (age, gender, ethnicity, income), measured their anthropometry (height, weight, BMI) and finally analysed their vitamin D and intact- Parathyroid hormone levels. Results. The prevalence of hypovitaminosis D was 16.9% among healthy teenagers with mean age of 15.9±1.39 years. Multivariate analysis showed female gender (adjusted OR, 95% CI): 23.7 (5.64, 100.3) and Chinese 0.24 (0.07, 0.84) were the significant predictors for hypovitaminosis D. Conclusion. The prevalence of healthy adolescents with hypovitaminosis D in Kota Bharu, Kelantan was 16.9% using the most recent cut off value of 30 nmol/L from the global consensus 2016. Female and Malay were the significant risk factors associated with hypovitaminosis D. Higher cut off value would result in overestimation of prevalence rate of hypovitaminosis D.